Measurement of the Flow of the River Canastra in Itapuranga (Goiás) as a strategy for Planning and Management of Hydrographic Basins - dos Reis de Souza, Josimar; Campos Ferreira, Edgar; Naiara Gonçalves dos Reis, Laís (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
This study aimed to measure the flow of the Canastra River, located in the municipality of Itapuranga (Goiás), from 2017 to 2018, using the float method. This river plays an important role in providing water for the urban area, for industry and for the irrigation of extensive areas of cultivation. Thus, the analysis focused on showing how these results can contribute to the planning and management of river basins. The methodology used for data collection was the estimation by the float method. The results obtained showed that in the wettest months the flow rate reached a relative average of 200 m³/s, with a maximum flow rate of 450 m³/s. In the dry months, especially in October 2018, the flow reached a minimum of 4.1 m³/s. The flow data of the watercourse allowed to show the extremes of the water source capacity, which has been increasingly under pressure from increasing demand for supply in the urban area of Itapuranga and also from industries and agricultural activities. Furthermore, this experimental study demonstrated how the use of techniques considered simple and cheap, such as the one used, emerge as possibilities for the practice of watershed management, available to managers, especially in small municipalities in the country with limited financial resources.